The assessment of interleukin-6, protein induced by vitamin k antagonist ii, and alpha-fetoprotein among hepatocellular carcinoma patients in Hospital Universiti Sains Malaysia - Wei, Lai Thing (2023)
Hepatocellular carcinoma (HCC) is a primary liver cancer that has a poor prognosis and a high prevalence among the Malaysians. At present, ultrasonography and serum Alpha-fetoprotein (AFP) are the only tools for HCC screening in this country. Serum Interleukin-6 (IL-6) and Protein Induced by Vitamin K Absence or Antagonist-II (PIVKA-II) are two potential serum biomarkers that were shown to be and AFP (Sn 73.08%, Sp 97.06%). Furthermore, the combination of all three serum biomarkers demonstrated the best diagnostic performance in HCC diagnosis (AUC=0.999). Conclusively, serum IL-6 and PIVKA-II have potential uses in HCC diagnosis as well as HCC treatment monitoring, especially when used in combination with serum AFP. elevated in HCC patients. However, there had been insufficient research on them in our population. This study aimed to assess the serum IL-6 and PIVKA-II levels among HCC subjects in Hospital USM , before and after treatment, as well compare their levels to those of serum AFP. Twenty six HCC subjects (Group 1) and thirty four healthy subjects (Group 2) were recruited. For Group 1, blood samples were collected and radiological assessments of their HCC lesions were done at the first visit and 6- weeks after their local treatment. For Group 2, only blood samples were only collected once. This study found that serum IL-6, PIVKA-II and AFP had higher median levels in HCC subjects than healthy subjects (p<0.001). IL-6 was not significantly correlated with radiological response post treatment (p=0.822). When comparing pre- and posttreatment values, serum IL-6 levels did not change significantly (p=0.328), whereas serum PIVKA-II levels were most significantly different (p<0.001) followed by serum AFP levels (p=0.007). In HCC diagnosis, PIVKA-II had the higher sensitivity and specificity (Sn 92.30%, Sp 94.11%) followed by serum IL-6 (Sn 84.62%, Sp 70.59%)